2009
DOI: 10.1038/onc.2009.23
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomeric DNA hypomethylation is not required for telomeric sister chromatid exchanges in ALT cells

Abstract: Most human tumor cells acquire immortality by activating the expression of telomerase, a ribonucleoprotein that maintains stable telomere lengths at chromosome ends throughout cell divisions. Other tumors use an alternative mechanism of telomere lengthening (ALT), characterized by high frequencies of telomeric sister chromatid exchanges (T-SCEs). Mechanisms of ALT activation are still poorly understood, but recent studies suggest that DNA hypomethylation of chromosome ends might contribute to the process by fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 49 publications
(80 reference statements)
1
52
1
Order By: Relevance
“…5A). This is consistent with recent observations showing that telomerase-positive human cancer cells carry hypermethylated subtelomeric DNA compared to telomerase-negative cancer or primary human cells (Vera et al 2008;Ng et al 2009;Tilman et al 2009). We then analyzed the methylation state of 61-29-37 repeats in human HCT116 cells knocked-out for DNMT1 (DNMT1 (Figs.…”
Section: Human Subtelomeres Contain Active Cpg-island Promoterssupporting
confidence: 81%
“…5A). This is consistent with recent observations showing that telomerase-positive human cancer cells carry hypermethylated subtelomeric DNA compared to telomerase-negative cancer or primary human cells (Vera et al 2008;Ng et al 2009;Tilman et al 2009). We then analyzed the methylation state of 61-29-37 repeats in human HCT116 cells knocked-out for DNMT1 (DNMT1 (Figs.…”
Section: Human Subtelomeres Contain Active Cpg-island Promoterssupporting
confidence: 81%
“…Comparisons between telomeric chromatin of ALT and telomerase expressing cells have revealed that ALT telomeres exhibit a more relaxed and accessible chromatin structure with reduced nucleosome density ( Figure 1B) [49]. Sub-telomeric patterns of DNA methylation appear heterogeneous and at a reduced level [45,50], as do the levels of H3K9me3 [49]. This correlates with the elevated levels of TERRA that are detected in ALT cells ( Figure 1B) [20].…”
Section: Box 1 Molecular Hallmarks Of Altmentioning
confidence: 64%
“…It is known that the methylation level of the D4Z4 array varies between normal cells, FSHD myoblasts and cervical carcinoma cells. 19,[29][30][31][32] However, the methylation status of the FR-MAR sequence was not studied earlier. The total DNA was isolated from several muscular and cervical cell lines and treated as described in Materials and methods section.…”
Section: Methylated Fr-mar Sequences Are Associated With Nmmentioning
confidence: 99%
“…Other genetic and epigenetic abnormalities affecting the subtelomeric region of chromosome 4q have also been observed in various pathologies including the Rett and ICF syndromes, 25 as well as in several types of cancer. [26][27][28][29][30][31][32] Here, we have tested whether mechanisms controlling the association of the FR-MAR to the NM could be similar in different cell types. We have used primary myoblasts from FSHD patients and cervical carcinoma cell lines where the D4Z4 repeat array can be either strongly methylated or demethylated.…”
Section: Introductionmentioning
confidence: 99%